2001
DOI: 10.1136/bmj.322.7300.1451
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive behavioural intervention to reduce sexually transmitted infections among gay men: randomised trial

Abstract: Objective To determine the effectiveness of a brief cognitive behavioural intervention in reducing the incidence of sexually transmitted infections among gay men. Design Randomised controlled trial with 12 months' follow up. Setting Sexual health clinic in London. Participants 343 gay men with an acute sexually transmitted infection or who reported having had unprotected anal intercourse in the past year. Main outcome measures Number of new sexually transmitted infections diagnosed during follow up and self re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 15 publications
(17 reference statements)
1
60
0
Order By: Relevance
“…In light of the present study's findings, data from another behavioral risk-reduction trial also points to the importance of examining sexual behavior within trial participants in HIV-prevention studies (Imrie et al, 2001). This study to reduce sexual risk among MSM used a one-day group workshop as a cognitive behavioral intervention to reduce STIs.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In light of the present study's findings, data from another behavioral risk-reduction trial also points to the importance of examining sexual behavior within trial participants in HIV-prevention studies (Imrie et al, 2001). This study to reduce sexual risk among MSM used a one-day group workshop as a cognitive behavioral intervention to reduce STIs.…”
Section: Discussionmentioning
confidence: 77%
“…This intervention, like many others, brought participants together for the intervention itself; a same-time intervention may be less financially and temporally burdensome than individual treatment. Imrie et al (2001) however, found that the individuals who received the group intervention actually had more new STIs post-study enrollment than those who did not. This study, however, did not report on whether men randomized to the intervention arm became sexually active with each other as a result of meeting during the group workshop.…”
Section: Discussionmentioning
confidence: 92%
“…Comparison with two studies of HIV negative homosexual men shows that sexual risk behaviour in this HIV population is particularly high. In a study of HIV negative homosexual men conducted in the same clinic 11 the risk of acquiring a bacterial STI in a 12 month period was 10% compared with 23% in this study, and a community survey of homosexual men in London has shown higher rates of STI and unprotected anal intercourse in HIV positive men compared with HIV negative men. 12 Concerning the link between HAART and treatment optimism, [4][5][6] we found that, in a population of HIV positive homosexual men who mostly rate their health as good, men on HAART are no more likely to have unprotected anal intercourse than those not on HAART.…”
Section: Discussionmentioning
confidence: 99%
“…Articles were excluded for not being a RCT or other suitable study, as specified in our inclusion criteria; not having the sufficient percentage of MSM in the study population; [137][138][139][140][141][142][143][144][145] not including a sufficient percentage of HIV-negative participants; [146][147][148][149][150][151][152][153][154][155][156] or not being an individually focused intervention, instead focusing on groups or structural factors. [157][158][159][160][161][162][163][164][165][166][167] Other reasons for exclusion, such as interventions not being brief, reporting a pilot trial, reporting non-HIV-specific data (e.g. if only alcohol-related outcomes were provided in a study assessing alcohol as well as HIV risk-related behaviours) or data were unobtainable despite our attempts to gain information from authors, were captured in our 'other' category.…”
Section: -106mentioning
confidence: 99%